Analisis Pengaruh Inflasi, Populasi dan Investasi Asing Langsung Terhadap Pengangguran di Indonesia - Larasati, Erlynda Rizky (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
The increasing number of unemployed is a serious problem for the development of developing countries, including Indonesia. The existence of unemployment due to the imbalance between supply and demand aspects both in terms of quantity and quality can lead to serious unemployment. Unemployment that is already very chronic and structural in nature will generally have a negative impact on environmental, social, economic and political development in a country. And very influential on the achievement of community welfare and development prospects in the country concerned. This study discusses